Development of an Integrated Monitoring System for Temperature, Air Humidity, Soil Moisture, and Light Intensity in Measurement Aids in Secondary Schools - Afriani, Melly; Hamdani, Dedy; Putri , Desy Hanisa (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2024)
responses to monitoring system media, and to assess students' learning outcomes after utilizing these media. The research method used is the Research and Development (R&D) method, using the ADDIE model, which includes five phases Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study consisted of 36 students in class X at SMA N 06 Bengkulu City. Data collection tools used in this study are questionnaires and tests of students' concept understanding. Data analysis techniques using a Likert scale with a scale of four.The results of the analysis stage showed that 77.8% of students agreed with development of learning media that has been designed. Development stage resulted in a validation score of 87.5% from the evaluator, which was categorized as very feasible. The student response to the media showed a percentage of 80.3%. The post-test results showed an average score of 84.16, with an average percentage score of 84%, categorized as good. This conclusion aims to evaluate students' conceptual understanding and responses, showing that instructional media can help students' conceptual understanding.